A Solid Alkylation: Highly Recyclable, Flow Chemistry‐Ready, Resin‐Supported Thioimidazoliums Alkylate Sulfur‐Centered Nucleophiles. Issue 35 (15th September 2022) - Cataldo, Vincenzo Alessandro; Taimoory, S. Maryamdokht; Mohammadzadeh, Sanam; Guterman, Ryan; Trant, John F.
Abstract: A series of readily regenerable thioimidazolium‐based ionic liquids, which can transfer alkyl groups to nucleophiles, are immobilized on crosslinked polystyrene beads. Different alkyl groups can be loaded onto the resin, highlighting the tunability of the material. The efficiency of these materials is demonstrated by their screening against a series of nucleophiles, showing a particular preference for thiols. Finally, these materials were evaluated for use under continuous flow conditions. The flexibility, ease of use, safety, and recyclability of these alkylating resins shows promise for their use in large scale and automated applications. Abstract : A mild alkylating agent can be immobilized and used to alkylate thiols and nitrogenous heterocycles, with low to poor ability to alkylate amines, and no reactivity against water or alcohols. Once depleted, the alkylating agent can be regenerated by treatment with alkyl iodide. The immobilized agent can be incorporated into a small flow reactor, allowing for increased ease of use.